Latin American and Caribbean Petroleum Engineering Conference 2009
DOI: 10.2118/121911-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of E-Beam Heavy Oil Upgrading

Abstract: Electron beam (E-Beam) heavy oil upgrading, which uses unique features of electron beam irradiation, can be a solution to minimize the critical problem of upgrading heavy oil. Enormous amounts of heavy oil reserves exist in the world, but the lack of cost-effective technologies hinders the development of heavy oil reserves. One of the critical problems of heavy oil or bitumen is that it takes large amounts of thermal energy and expensive catalysts to upgrade. E-Beam processing will allow lowering the thermal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…From an economical perspective, some authors reported radiation methods to be more favorable compared to catalytic processes. , More specifically, Yang et al showed that electron beam irradiation, when performed in an industrial scale, could decrease the upgrading cost by 31%. They also suggested a practical design to use electron irradiation in dynamic flow processing units to upgrade heavy fluids in pipelines . In another work, Yang et al coupled heat transfer and radiation Monte Carlo simulation to model electron beam upgrading process of multiphase and single-phase hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…From an economical perspective, some authors reported radiation methods to be more favorable compared to catalytic processes. , More specifically, Yang et al showed that electron beam irradiation, when performed in an industrial scale, could decrease the upgrading cost by 31%. They also suggested a practical design to use electron irradiation in dynamic flow processing units to upgrade heavy fluids in pipelines . In another work, Yang et al coupled heat transfer and radiation Monte Carlo simulation to model electron beam upgrading process of multiphase and single-phase hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%